Participatory forest resource management for District development - a case study of the Assin-Fosu District - Reyes, Hector E. Castanon (2011)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirements for the award of Master of Science degree in Development Planning and Management.